Rekultywacja terenów pogórniczych w KWB "Sieniawa" sp. Z o.o. = The reclamation of post-mining areas of KWB "Sieniawa" sp. Z o.o. - Galiniak, Grzegorz; Jarosz, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the actual state of reclamation of the post-mining areas of the lignite strip mines of KWB "Sieniawa" Sp. z o.o. Discussed is the development of "Sieniawa" Strip Mine, the issues pertaining to transformation of the land surface resulting from the conducted mining operation, as well as the overall prevailing conditions that are related to land reclamation and development. Presents the data that characterize the reclamation of lands for forestry, agriculture and water management purposes.
Keywords: górnictwo odkrywkowe; rekultywacja; tereny pogórnicze; reclamation; opencast mining; post mining terrains